Avaliação na educação infantil a documentação pedagógica e as práticas docentes no contexto dos direitos das crianças - Moreira, Juliana Corrêa (2015)
Currently, early childhood education has been increasing more and more in the educational and political scene, consolidating itself as a useful investigative field, and bringing to the agenda many questions that reveal its potential. Among these emerges the theme of evaluating, a complex concept that involves a multitude of ideas and purposes, especially under the very young babies and children education, given its specificity. Thus, this master's research investigated the evaluation in early childhood education and its dialogue with the pedagogical practices in collective contexts with children 0 to 3 years. The methodological basis of this study adopted the agenda in a qualitative approach, guided by the approach to educational action research (EAR), using as production techniques and data collection participant observation and journaling field. In the review process of the materials produced in the course of the EAR cycles and discussion of the results of the research, we follow the method of content analysis (BARDIN, 1977; TRIVIÑOS,2010). In the search for understanding the constitution of the search field in historical and theoretical perspective, we support the studies of BARBOSA (2008; 2009); Jr. KULMANN (2010); CAMPOS (2014), among others. On the evaluation of the subject in kindergarten and its dialogue with the quality of these contexts use the studies of Hoffmann (2001, 2008, 2012); BONDIOLI (2004); Zabalza (1998); among others, as well as and turning on the documents and legal publications that refer to the evaluation of the subject in this educational stage. In addition to further study on the topic, we seek to relate and highlight the importance of evaluation within the pedagogical practices in early childhood education, understanding it as a key element in the training of teachers and determining the qualification of educational contexts.